Pemanfaatan informasi genom untuk eksplorasi struktur genetik dan asosiasinya dengan performan ternak di Indonesia - Pita Sudrajad; Slamet Diah Volkandari; Muhammad Cahyadi; Amrih Prasetyo; Komalawati Komalawati; Sujatmiko Wibowo; Subiharta Subiharta (Livestock and Animal Research, 2021)
Currently, livestock development strategies in various countries have made extensive use of molecular technology at the genome level. Genome contains information of the entire DNA within the livestock cells, therefore it is believed that this technology is able to map the relationship between genotypes and phenotypes more precisely. Genome technology describes all genes in the body and how they interact and influence the growth and performance of livestock. Genome information can support every effort for livestock development including breeding, optimizing the feed nutrition efficiency through the use of feed ingredients more efficiently, and improving reproduction performance. In terms of efforts to improve livestock performance in Indonesia, genomic technology can be utilized to increase the accuracy and efficiency of livestock selection programs. The application of genomic technology in Indonesia still encounters many constraints, including lack of confidence on the benefits that can be generated, the high cost, as well as the incomplete recording data of livestock performance. Currently, researchers in Indonesia have started utilizing genome information to explore the genetic structure of livestock and its association with the livestock performance. Support from all stakeholders are needed to minimize the limitations of genome technology application on livestock in Indonesia.